Enlarging the basin of attraction by a uniting output feedback controller. (April 2018) - Davó, Miguel A.; Prieur, Christophe; Fiacchini, Mirko; Nešić, Dragan
Abstract: We consider a system for which two predesigned stabilizing output feedback controllers with bounded domains of attraction are known. One renders the system asymptotically stable with some desired performance, and the other provides ultimate boundedness with larger domain of attraction. Assuming that two subsets of the domains of attraction are known, one larger than the other, this work states the problem of combining both controllers with the goal of guaranteeing asymptotic stability properties in the largest subset while the desired performance is locally achieved. We design a switching logic between the controllers that solves the problem, based on the existence of a local tunable observer. The resulting control law is defined by a hybrid output feedback controller. The effectiveness of the proposed solution is illustrated by a numerical example.